Common wetland plants of Colorado's eastern plains: a pocket guide - Culver, Denise R., author; Colorado Natural Heritage Program, publisher (Colorado State University. Libraries, 2018)
The Pocket Guide highlights common wetland plants, both native and non-native located within the Eastern Plains. It is designed to help landowners and other wetland managers correctly identify common wetland plants, manage for preferred species, and identify noxious ones. The Pocket Guide contains 148 species with 6 key characteristics (with bolded highlights ofdiagnostic characters), similar species, habitat and ecology comments, and management comments.
Prepared for: U.S. Environmental Protection Agency, Region 8.
2nd edition.
Keywords: Colorado; wetland plants; identification